Public utility as economic category - Wojciechowski, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the article is an attempt to present more enhanced characteristics of the concept of public utility. It is a term that is also used in economic literature to describe a particular type of economic activity in the public sphere. However, despite the legal definition the category of public utility is not satisfactory and variously interpreted. The discussion conducted in the article is twofold. First, it refers to the formula of public utility enterprises; secondly, it refers to the analysis of the essential characteristics of this sphere of activity. To achieve this goal the author used literature review and legal acts. As a result, the findings concerning the conditions for the functioning of the public utility were presented and the author made an attempt to redefine the term. The article highlights the merits of the enterprise model in a separate legal regime, appropriate to the specific nature of public utility as derogation from the logic of the market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 78-87
Keywords: public interest; public utility; public service; authority; enterprise; collective needs; interes publiczny; usługi komunalne; władza; przedsiębiorstwo; potrzeby zbiorowe